A New Reliability Ratio Weighted Bit Flipping Algorithm for Decoding LDPC Codes. (17th May 2021) - Aqil, Chakir; Akharraz, Ismail; Ahaitouf, Abdelaziz
Abstract : In this study, we propose a "New Reliability Ratio Weighted Bit Flipping" (NRRWBF) algorithm for Low-Density Parity-Check (LDPC) codes. This algorithm improves the "Reliability Ratio Weighted Bit Flipping" (RRWBF) algorithm by modifying the reliability ratio. It surpasses the RRWBF in performance, reaching a 0.6 dB coding gain at a Binary Error Rate (BER) of 10 −4 over the Additive White Gaussian Noise (AWGN) channel, and presents a significant reduction in the decoding complexity. Furthermore, we improved NRRWBF using the sum of the syndromes as a criterion to avoid the infinite loop. This will enable the decoder to attain a more efficient and effective decoding performance.